Transformation and Depuration of Paralytic Shellfish Toxins in the Geoduck Clam Panopea globosa From the Northern Gulf of California - Medina-Elizalde, Jennifer; García-Mendoza, Ernesto; Turner, Andrew D.; Sánchez-Bravo, Yaireb Alejandra; Murillo-Martínez, Ramón (Frontiers in Marine Science, 2018)
In January 2015 a harmful algae bloom (HAB) of the dinoflagellate Gymnodinium catenatum occurred in the Northern Gulf of California (NGC). This species produces paralytic shellfish toxins (PSTs) a group of potent neurotoxins. The harvesting and commercialization of geoduck Panopea globosa are important economic activities in this region. These activities were prohibited for several months due to the accumulation of PSTs in clam tissues. We analyzed PSTs concentrations in P. globosa collected on a weekly basis during 2015 near San Felipe, Baja California. The goal of the study was to evaluate the transformation and depuration characteristics of PSTs in the geoduck tissues. Three organisms from each sampling date were dissected and the PST content was evaluated in the visceral mass and siphon by high performance liquid chromatography with post column oxidation (HPLC-PCOX). Ten selected samples were also analyzed by hydrophilic interaction chromatography coupled to tandem mass spectrometry (HILIC-MS/MS). Toxicity in the siphon was lower than 800 µg STX eq kg-1 (the regulatory limit for PSTs) in all samples. In contrast, the maximum toxicity in the visceral mass exceeded 21 times this limit. It took 210 days to reach the regulatory limit after a maximum toxicity of 16,740 µg STXeq kg-1 was detected. Therefore, P. globosa is a slow detoxifier bivalve with a depuration rate of 4.26 day-1 (adjusted to an exponential decay model; r2=0.80). C1&2 were the most abundant analogues in siphon and viscera samples collected close to the HAB occurrence. The concentration of these analogues decreased and more toxic analogues as GTX5, dcGTX2 and dcSTX were detected. M-type analogs were detected by HILIC-MS/MS and represented up to 75% of total PSTs in some samples. M-type analogs contributed to 48% of toxicity estimated in the sample. We report for the first time the depuration rate, PSTs profile and its change over time in P. globlosa. This information is essential to characterize the metabolism of toxins in this economically important bivalve but also to develop management plans for the fishery if the organism is going to be recurrently exposed to PSTs producing blooms, as seems the case for the NGC.